Diagnostic and therapeutic procedures in adolescents and young adults with changes of the breast - Gralec, Artur; Czerwionka-Szaflarska, Mieczysława; Zawadzka-Gralec, Anna; Laskowski, Ryszard; Zegarski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2010)
Mammary gland diseases are an important health problem in each age group. In older patients malignant tumours are dominant, whereas in children and adolescents congenital defects, cysts and benign tumours are observed. Malignant tumours are rare before 25 years of age but despite sporadic prevalence are a serious problem because they are more aggressive and are associated with a serious prognosis. Problems of mammary gland diseases in adolescents and young adults are nowadays not well known and diagnostic and therapeutic procedures are difficult due to the lack of unified standards. This paper presents a review of current opinions on diagnostic management in developmental age. The authors also present an algorithm for diagnostic and therapeutic procedures of mammary gland changes in adolescents and young adults.